Paradoxes of Children's Vulnerability. Issue 3 (3rd July 2019) - Macleod, Colin
ABSTRACT: This paper explores the manner in which the special vulnerabilities of children ground duties to protect them from threats to their well-being. I distinguish three kinds of risk: pointless risks, required risks and unnecessary risks. I argue that a seemingly plausible view that holds that adults should strive to protect children from both pointless risks and unnecessary risks is mistaken. Instead respect for children as juvenile but not fully mature agents permits exposing children to some unnecessary risks. Moreover, the limited prerogatives that parents have to shape the values of their children also permits exposing children to some unnecessary risks.